2021
DOI: 10.1021/acs.energyfuels.0c03299
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Scale X-ray Imaging of Wetting Alteration and Oil Redistribution during Low-Salinity Flooding of Berea Sandstone

Abstract: Observations over a range of scales show that lowering the salinity of injected water can alter the wetting state of a rock, making it more water-wet. However, there remains a poor understanding of how this alteration affects the distribution of fluids over the pore and pore-network scale and how this wetting alteration leads to oil recovery. In this work, we observe how oil and brine redistribute in the pores of rocks in response to low-salinity flooding. We use X-ray μ-CT scanning to image tertiary lowsalini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…X-ray imaging has been previously used to study LSW [49][50][51][52][53], with only a few studies on carbonate rocks [27,[54][55][56]. Using micro-CT imaging, Qin et al [57] compared high and low salinity flooding at reservoir conditions.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray imaging has been previously used to study LSW [49][50][51][52][53], with only a few studies on carbonate rocks [27,[54][55][56]. Using micro-CT imaging, Qin et al [57] compared high and low salinity flooding at reservoir conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it has strong potential for applications in material sciences, such as salt or mineral hydration, and geological phenomena, such as fluid migration in fractures within shale . In addition to acquiring knowledge on these materials, this work has implications for industrial applications of non-destructive observation , and may enable numerical simulation of various physical processes in digital objects. …”
Section: Resultsmentioning
confidence: 99%
“…This was done to ensure the visibility of the water droplet in oil. Literature has shown that the effect of the modified salinity brines on oil recovery can be hindered, unless the initial oil-wet conditions are achieved . That is why, in each case, the acidity of the mixture was adjusted to a TAN of 1.5 mg KOH/g by using stearic acid to ensure that oil-wet conditions are established during the aging process. , The interfacial tension (IFT) of each mixture with seawater has been tested using the pendant drop method and is presented on Figure .…”
Section: Methodsmentioning
confidence: 99%